2013
DOI: 10.1039/c2sm27021h
|View full text |Cite
|
Sign up to set email alerts
|

Exploring locked nucleic acids as a bio-inspired materials assembly and disassembly tool

Abstract: Oligonucleotides hold great promise as a recognition-based biomaterials assembly and disassembly tool. Chemically modified oligonucleotides such as locked nucleic acids (LNA) provide the added advantage of nuclease resistance. In the current study, we focus on programming the assembly and disassembly of LNA-linked colloidal particles as a function of sequence composition. We find that incorporation of LNA residues ($30%) into either one or both primary hybridization partner strands results in a higher duplex d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…For example, as illustrated in Figure 1 , a methylene bridge between the 2′O and 4′C of the sugar ring conformationally locks the sugar into an N-type pucker [ 11 ], resulting in a locked nucleic acid (LNA). In contrast to the varying thermal stability effects of specific chemical substitutions in 2′O position of sugar groups discussed above, LNA substitutions result in oligonucleotides with both higher duplex stability and superior nuclease resistance [ 32 , 33 , 34 ]. Despite differences in their duplex densities, high throughput flow cytometry studies of microspheres functionalized with single-stranded DNA or DNA/LNA mixmer probes indicated that the kinetics of duplex formation with either pure DNA or DNA/LNA mixmer targets were comparable across nearly all sequence combinations [ 35 ].…”
Section: General Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as illustrated in Figure 1 , a methylene bridge between the 2′O and 4′C of the sugar ring conformationally locks the sugar into an N-type pucker [ 11 ], resulting in a locked nucleic acid (LNA). In contrast to the varying thermal stability effects of specific chemical substitutions in 2′O position of sugar groups discussed above, LNA substitutions result in oligonucleotides with both higher duplex stability and superior nuclease resistance [ 32 , 33 , 34 ]. Despite differences in their duplex densities, high throughput flow cytometry studies of microspheres functionalized with single-stranded DNA or DNA/LNA mixmer probes indicated that the kinetics of duplex formation with either pure DNA or DNA/LNA mixmer targets were comparable across nearly all sequence combinations [ 35 ].…”
Section: General Introductionmentioning
confidence: 99%
“…Using a large combinatorial array of different toehold lengths and position-dependent LNA substitutions, Olson et al demonstrated the range of displacement kinetics possible in oligonucleotide solutions [ 62 ]. By immobilizing nearly complementary DNA/LNA mixmers on microspheres and nanoparticles, Eze and Milam formed colloidal satellite assemblies susceptible to displacement-driven colloidal disassembly by perfectly complementary DNA/LNA targets under isothermal conditions [ 34 ]. Using chimeric blends of right-handed DNA and left-handed DNA in their double-stranded probes, Young and Sczepanski added an elegant chirality-dependence to their displacement approach [ 63 ].…”
Section: General Introductionmentioning
confidence: 99%
“…The few exceptions are limited to complex melting/aggregation behaviours controlled by suitably designed DNA coatings that allow step-wise activation of the interactions, either in response to temperature changes 12 or aided by external fields and photoactivated permanent linkers 14 . Melting can also be controlled through competing linkages formed within the particles 15 16 or with DNA strands dispersed in solution 17 18 19 20 . Beyond melting/aggregation, structural responsiveness to external stimuli has only been achieved for nanoparticle aggregates, where competing linkers added in solution are able to significantly change the length of DNA bonds and thereby the density of the aggregates 21 .…”
mentioning
confidence: 99%
“…The use of LNAs for the assembly and disassembly of polystyrene nanoparticles, using short duplexes that are exact matches or contain one centre mismatch, was explored in a study conducted by Eze and Milam. 200 Initially, primary hybridisation and competitive displacement activities involving two matched or mismatched DNA–DNA, LNA–LNA, and LNA–DNA strands were quantified as a function of sequence complementarity and length. Programmable colloidal assembly and disassembly of polystyrene nanoparticles was achieved by successfully tuning and optimising the hybridisation affinity, sequence length, duplex concentration and number of LNA residues found in the probe and target strands.…”
Section: Nucleic Acid Backbone Modificationsmentioning
confidence: 99%